Improving screening for diabetes in cystic fibrosis. Issue 5 (8th June 2015) - Abdulhamid, Ibrahim; Guglani, Lokesh; Bouren, Jennifer; Moltz, Kathleen C
Abstract : Purpose: – Annual screening for cystic fibrosis-related-diabetes (CFRD) using oral glucose tolerance test (OGTT) is recommended, but national testing rates are low. The purpose of this paper is to implement the quality improvement (QI) initiative to improve cystic fibrosis (CF) annual screening rates among patients at one CF center. Design/methodology/approach: – To improve screening for CFRD at the CF Center, the authors used the Dartmouth Microsystem Improvement Ramp method and formed a collaborative working group. A process map was created to outline the steps and a fishbone analysis was performed to identify barriers and to utilize resources for implementing new interventions. Findings: – Prior to these interventions, 21 percent of eligible patients had completed annual screening and after the intervention, it rose to 72 percent. The initial completion rate with the first prescription was only 50 percent, but it improved steadily to 54/75 (72 percent) in response to reminder letters sent six weeks after the initial script was given. Practical implications: – Close tracking and reminder letters can improve adherence with annual OGTT screening for CFRD among CF patients, with special emphasis on high-risk patients. Originality/value: – There should be a special emphasis on screening for CFRD in high-risk CF patients (those with low BMI or higher age). This QI initiative brought about several operational changes in the annual OGTT screening process that have now become the standard operating procedure at the center.